Effect of electrophysiological mapping on non-transmural annulus ablation and atrial fibrillation recurrence prediction after 6 months of Cox-Maze IV procedure - Sun, Zhishan; Fan, Chengming; Song, Long; Zhang, Hao; Jiang, Zenan; Tan, Haoyu; Sun, Yaqin; Liu, Liming (Frontiers in Cardiovascular Medicine, 2022)
Objective: To observe the safety and efficacy of electrophysiological mapping following Cox-Maze IV procedure and investigate whether a correlation exists between recurrence of atrial fibrillation (AF) with the completeness of bi-directional electrical isolation and the inducibility of AF immediately after the Cox-Maze IV procedure. Methods: 80 consecutive patients who suffered from aortic valve or mitral valve disease and persistent AF were randomly enrolled into control group and electrophysiological mapping following Cox-Maze IV group (Electrophysio-Maze group). In Electrophysio-Maze group, patients underwent concomitant Cox-Maze procedure and following electrophysiological mapping of ablation lines in mitral isthmus, left atrial “box” and tricuspid annulus. If the bi-directional electrical isolation of tricuspid annulus ablation line in incomplete, whether to implement supplementary ablation will be independently decided by operator. Before and after Cox-Maze IV procedure, AF induction was performed. All patients in both groups were continuously followed-up and underwent electrocardiogram (ECG) Holter monitoring after 6 months. Results: 42 Electrophysio-Maze patients and 38 controls were enrolled. Compared with patients in control group, there were shorter hospital stay, better cardiac remodeling changes and higher relief from AF during follow-up period of 6 months in Electrophysio-Maze group. Within the Electrophysio-Maze group, the rate of incomplete bi-directional electrical isolation of “box” ablation lines was zero, and the rate of incomplete bi-directional electrical isolation of mitral isthmus ablation line or tricuspid annulus ablation line was 23.8%. After two cases of successful complementary ablation on tricuspid annulus ablation line, the final incomplete bi-directional electrical isolation of annulus ablation lines was 19.0%. There were correlation between late AF recurrence after 6 months with incomplete bi-directional electrical isolation of annulus ablation lines and AF induction immediately after Cox-Maze IV procedure. Conclusion: Electrophysiological mapping following Cox-Maze procedure is safe and effective. Electrophysiological mapping in Cox-Maze procedure can find out the non-transmural annulus ablation lines by assessing the completeness of bi-directional electrical isolation of ablation lines, guide supplementary ablation and predict atrial fibrillation recurrence after 6 months.